Dietary trans fatty acid intakes and cancer risk: results from the NutriNet-Santé cohort. (20th October 2021) - Wendeu-Foyet, G; Chajes, V; Huybrechts, I; Debras, C; Chazelas, E; Srour, B; Agaësse, C; Druesne-Pecollo, N; Deschasaux-Tanguy, M; Touvier, M
Abstract: : Dietary trans fatty acids (TFAs) are either natural (ruminant sources) or industrially generated by partial hydrogenation of vegetable oils. Increasing evidence demonstrated their role as cardiovascular risk factors. Their involvement in cancer etiology is suspected, but epidemiological evidence is limited so far. We aimed to investigate the associations between different types of TFAs (total, ruminant [rTFAs], industrial [iTFAs] and corresponding specific isomers) and the risk of cancer in the NutriNet-Santé prospective cohort (2009-2020). Overall, 104, 909 participants were included. Usual TFA intake was estimated from validated repeated 24-h dietary records. Associations between sex-specific quartiles of dietary intake of TFA and cancer risk were assessed using multi-adjusted Cox proportional hazard models. A total of 3, 374 incident cancer cases occured during follow-up (including 982 breast and 405 prostate cancers). Total TFAs was associated with higher prostate cancer risk (1.34[1.25;1.87] Ptrend=0.005). rTFAs were associated with increased overall cancer risk (HRfor quartile 4 versus 1: 1.21[1.06;1.39] Ptrend=0.03), in particular the conjugated linoleic acid isomer (CLA) (1.19[1.04;1.36] Ptrend=0.04). These associations were specifically observed for breast cancer, in particular before menopause (rTFAs: 1.78[1.11;2.87] Ptrend=0.006; CLA: 2.013[1.25;3.23] Ptrend=0.003). Several iTFAs were associated with overall (1.18[1.06;1.31] Ptrend=0.02 for transdocosenoic acid), breast (isomer 18:2t: 1.30[1.06;1.58] Ptrend=0.01; hexadecenoic acid: 1.28[1.05-1.56] Ptrend=0.02) and prostate (transdocosenoic acid: 1.52[1.09;2.12] Ptrend=0.07) cancer risks. In this large prospective study, several types of TFAs were associated with increased overall, breast and prostate cancer risks. Although further studies are needed to better understand underlying mechanisms, these results support the WHO's goal of achieving industrially produced TFAs elimination from food supplies. Key messages: Higher intake of dietary trans fatty acids is associated with an increased risk of various cancers. Our findings support WHO's global recommendation of eliminating industrially produced TFAs by 2023.